Mandibular CT-Based radiomorphometric and density indices for opportunistic osteoporosis screening - Sen, Yakup; Baybars, Sumeyye Cosgun; Karaagac, Seda Sogukpinar (Bmc, 2026)
Purpose This study aimed to evaluate the association between mandibular radiomorphometric indices (CTMI, CTI(S), CTI(I)) and trabecular Hounsfield Unit (HU) values obtained from computed tomography (CT) scans with osteoporosis as defined by dual-energy X-ray absorptiometry (DEXA). Methods This retrospective study was conducted at the Department of Radiology, Faculty of Medicine, F & imath;rat University, using routine head and neck CT scans. All participants underwent DEXA at the L1-L4 vertebral levels according to World Health Organization (WHO) criteria. The osteoporosis group consisted of 50 patients with a T-score <= -2.5 and a clinical diagnosis of osteoporosis by the Physical Therapy Department, while the control group comprised 50 individuals with T-scores >= -1 and no diagnosis of osteoporosis. Bilateral measurements of CTMI, CTI(S), and CTI(I) were averaged, and HU values were recorded from predefined mandibular regions. Results All radiomorphometric indices and HU values were significantly lower in osteoporotic individuals compared to the control group. ROC analysis demonstrated threshold values for CTMI <= 3.35 mm (sensitivity: 86%, specificity: 98%), CTI(I) <= 0.36 (sensitivity: 78%, specificity: 92%), and CTI(S) <= 0.27 (sensitivity: 78%, specificity: 98%). Threshold HU values were observed as <= 337 for the mandibular angle, <= 209 for the mandibular corpus, and <= 470 for the interradicular area between teeth 3 and 4. Among these regions, the mandibular angle showed the highest area under the curve (AUC: 0.857; sensitivity: 90%). Conclusion Mandibular CT-derived radiomorphometric and densitometric measurements are associated with osteoporosis as defined by DEXA and may provide complementary information within an opportunistic screening framework.
Keywords: Osteoporosis; DEXA; Bone mineral density; Computed tomography; Mandibular index; Hounsfield unit